2005
DOI: 10.1081/copd-200050740
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Management of Co-Morbid Depression in COPD

Abstract: Individuals with COPD have a higher prevalence of co-morbid depression than either the general population or patients with other chronic illnesses. The best estimates report a prevalence of approximately 40% in COPD patients, compared to 15% in the general population. Depression in COPD patients leads to a lower quality of life, greater objective impairment in function, and decreased adherence to therapeutic interventions. While many depressed COPD patients have been treated empirically with antidepressants--s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
(18 reference statements)
1
38
0
Order By: Relevance
“…Other studies that have demonstrated significant improvement have been limited by small numbers of participants [32]. In the absence of strong evidence-based guidance, an algorithm parallel to that used for non-COPD depressive patients is the best clinical strategy [33 ].…”
Section: Management Of Depression In Chronic Obstructive Pulmonary DImentioning
confidence: 99%
“…Other studies that have demonstrated significant improvement have been limited by small numbers of participants [32]. In the absence of strong evidence-based guidance, an algorithm parallel to that used for non-COPD depressive patients is the best clinical strategy [33 ].…”
Section: Management Of Depression In Chronic Obstructive Pulmonary DImentioning
confidence: 99%
“…About 40% of patients with COPD are found to have depression, compared to a prevalence of about 15-20 % in the general population 14 . We found a prevalence of close to 90% of at least mild depression (as measured on the Hamilton depression scale) in patients admitted with COPD 15 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Patients with depression also characteristically make fewer attempts to improve their health. [4][5][6] Therefore, examining symptoms of depression is an important part of comprehensive COPD treatment.…”
Section: Introductionmentioning
confidence: 99%